Mitigating life cycle GHG emissions of roads to be built through 2030: Case study of a Chinese province. (1st October 2022) - Huang, Yuqiao; Wolfram, Paul; Miller, Reed; Azarijafari, Hessam; Guo, Fengdi; An, Kangxin; Li, Jin; Hertwich, Edgar; Gregory, Jeremy; Wang, Can
Abstract: The expansion of road networks in emerging economies such as China causes significant greenhouse gas (GHG) emissions. This development is conflicting with China's commitment to achieve carbon neutrality. Thus, there is a need to better understand life cycle emissions of road infrastructure and opportunities to mitigate these emissions. Existing impact studies of roads in developing countries do not address recycled materials, improved pavement maintenance, or pavement-vehicle interaction and electric vehicle (EV) adoption. Combining firsthand information from Chinese road construction engineers with publicly available data, this paper estimates a comprehensive account of GHG emissions of the road pavement network to be constructed in the next ten years in the Shandong province in Northern China. Further, we estimate the potential of GHG emission reductions achievable under three scenario sets: maintenance optimization, alternative pavement material replacement, and EV adoption. Results show that the life cycle GHG emissions of highways and Class 1–4 roads to be constructed in the next 10 years amount to 147 Mt CO2-eq. Considering the use phase in our model reveals that it is the dominant stage in terms of emissions, largely due to pavement-vehicle interaction. Vehicle electrification can only moderately mitigate these emissions. Other stages, such as materials production and road maintenance and rehabilitation, contribute substantially to GHG emissions as well, highlighting the importance of optimizing the management of these stages. Surprisingly, longer, not shorter maintenance intervals, yield significant emission reductions. Another counter-intuitive finding is that thicker and more material-intensive pavement surfaces cause lower emissions overall. Taken together, optimal maintenance and rehabilitation schedules, alternative material use, and vehicle electrification provide GHG reduction potentials of 11%, 4%–16% and 2%–6%, respectively. Highlights: Road construction implies significant amounts of GHG emissions. China's road expansion plans are at odds with its target of GHG neutrality. We assess GHG emissions of Shandong's roads to be constructed through 2030. We combine life cycle assessment based on primary data with a new optimization model. Individual mitigation measures can reduce life cycle GHG emissions by up to 16%.